Leadership Readiness for Independent Curriculum Implementation in Indonesian Early Childhood Education Institutions - Anwar, Rosyida Nurul (GENIUS: Indonesian Journal of Early Childhood Education, 2025)
This study explores the readiness of kindergarten principals in Madiun Regency, Indonesia, to implement the Independent Curriculum (Kurikulum Merdeka) in early childhood education institutions. Using a mixed-methods approach, data were collected through questionnaires, interviews, observations, and document analysis from 304 kindergartens. The findings show that principals demonstrated readiness by participating in curriculum training, encouraging independent learning through the Merdeka Mengajar Platform, organizing comparative studies with School Mover Program (PSP) institutions, initiating learning communities, improving learning infrastructure, and engaging parents and stakeholders. These efforts reflect a proactive commitment to fostering student-centered and developmentally appropriate practices in line with the Independent Curriculum. The study highlights the pivotal role of school principals in leading systemic educational reform at the early childhood level and emphasizes the importance of leadership, collaboration, and contextual adaptation. It recommends strengthening differentiated instruction, family-school partnerships, and project-based learning to ensure sustainable curriculum integration.